2020
DOI: 10.1002/bies.201900237
|View full text |Cite
|
Sign up to set email alerts
|

Lipophilic Environmental Chemical Mixtures Released During Weight‐Loss: The Need to Consider Dynamics

Abstract: Intentional weight loss can increase health risk in the long‐term, despite short‐term benefits, because human adipose tissue is widely contaminated with various lipophilic environmental contaminants, especially persistent organic pollutants (POPs). Recently, chronic exposure to low POPs has emerged as a new risk factor for common metabolic diseases and cardiovascular diseases. The amount of POPs released from adipocytes to the circulation increases during weight loss, thereby increasing POPs exposure of other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…It could be hypothesized that pollutants that were accumulated in the fat tissue are slowly released during long-term fasting. In another study, calorie restriction-induced weight loss provoked a release of persistent organic pollutants from adipocytes and increased their levels in the circulation ( 45 ). It was reported that the increase of toxic chemicals in serum is proportional to the weight loss ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It could be hypothesized that pollutants that were accumulated in the fat tissue are slowly released during long-term fasting. In another study, calorie restriction-induced weight loss provoked a release of persistent organic pollutants from adipocytes and increased their levels in the circulation ( 45 ). It was reported that the increase of toxic chemicals in serum is proportional to the weight loss ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, calorie restriction-induced weight loss provoked a release of persistent organic pollutants from adipocytes and increased their levels in the circulation ( 45 ). It was reported that the increase of toxic chemicals in serum is proportional to the weight loss ( 45 ). A weight loss of 10% was related to an increase of persistent organic pollutants up to 20% in blood over 4–6 months ( 46 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this clinical trial, the intensive weight loss group failed to attain any benefit on the development of cardiovascular diseases compared to the control group, despite an improvement in many known risk factors for cardiovascular diseases. 33 Therefore, the ideal strategy of weight management should consider both fat mass and the dynamics of POPs.…”
Section: Dilemma Related To Weight Lossmentioning
confidence: 99%
“…As noted by Lee et al. in this issue, persistent organic pollutants (POPs) released from adipose during weight loss in type 2 diabetic (T2DM) patients may attenuate cardiovascular (CV) benefits [ 1 ] that should accompany >5% weight reduction and concomitant fall in CV disease risk factors. [ 2 ] POP contributions to CV complications is a valuable and timely topic to explore, given the slow rate of POP elimination from the food chain and epidemiological evidence that low dose POPs are additional risk factors for metabolic [ 3 ] and CV diseases.…”
mentioning
confidence: 99%
“…[ 5 ] A moderate, rather than low‐fat, and largely plant‐based diet with intermittent fasting or caloric restriction is envisaged by Lee et al. [ 1 ] to facilitate biliary POP excretion, provide protective phytochemicals that induce or enhance cellular defense mechanisms, and reduce POP intake through avoidance of animal‐derived fats. Such POP‐targeted interventions may have additional benefits, such as reducing pancreatic damage and insulin resistance.…”
mentioning
confidence: 99%